Bacteriological Quality, Safety and Anti-microbial Resistance of Microorganisms Isolated from Various Animal Derived Food Products - Akkina, Rajani Chowdary; Vijayalakshmi , Payala; Padmaja, Indugula Jyothi (Current Perspectives in Agriculture and Food Science Vol. 1, 2022)
The present chapter described the isolation of bacteria that harbour various animal food products like meat, chicken and seafoods collected from the abattoir, butcher shops and local seafood market and to determine the antimicrobial resistance pattern of isolated pathogens which are responsible for various food borne illnesses in human beings. The main obstacle to reducing the possibility of drug resistance is the prudent use of antimicrobial drugs. A total of forty raw animal product samples were obtained from the abattoir, butcher shops and local fish market of Visakhapatnam. The study's samples include raw chicken, pork, crab, prawns, and several kinds of fish. A traditional random sampling strategy was applied to acquire the study samples. All of the samples were immediately processed using accepted microbiological procedures. The bacteria isolation and characterization were achieved by evaluating morphological properties with staining methods, cultural characteristics by isolating and growing the pathogenic microorganisms in various selective and differential culture conditions. Antimicrobial susceptibility testing was performed by the Kirby -Bauer method by following Clinical and Laboratory Standards Institute (CLSI) standards. EDTA-Disc Potentiation Test and Imipenem-EDTA Double disc synergy test are used to determine the metallo beta-lactamase synthesis of isolated microorganisms. Pseudomonas aeruginosa (18) followed by Vibrio species (14) and few isolates belong to Enterobacter species (4). In the present study, the majority of the microbiological isolates were multidrug resistant. The isolates from abattoir environments, slaughterhouses, and fish markets were discovered to exhibit variable resistance patterns to the antibiotics used in the current study, including aminoglycosides, macrolides, \(β\)-lactams, cephalosporins, and quinolones, while most of them were still susceptible to the carbapenem antibiotic imipenem. Antimicrobial resistance (AMR) prevents the creation and assessment of effective therapies. If such a correlation can be established, then the tracking of antibiotic usage and consumption data might be furthermore employed as a surrogate indicator for the risk of possible antibiotic resistance (ABR) emerging.